2015
DOI: 10.2136/sssaj2014.09.0348
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Manure Impacts on Soil Aggregates and Aggregate-Associated Carbon and Nitrogen

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. Permission for printing and for reprinting the material contained herein has been obtained by the publisher. Long-Term Manure Impacts on Soil Aggregates and Aggregate-Associated Carbon and Nitrogen Soil & Water Management & Conservation Long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…stover incorporation and roots, as can be seen for the mineral fertilizer treatment (Table ). This is the key point of our research which distinguishes it from the works of others authors (Whalen & Chang, ; Hou et al, ; Tripathi et al, ; Gelaw et al, ; Mikha et al, ) where soil aggregation was related to total SOC. It also reinforces the warning of Pulido Moncada et al () when using the SOC as an estimator of aggregate stability, that specific fractions of the SOC can be the stabilizing agent as, in our case, the light fraction despite the increment of the most stable SOC fraction at the highest manure rate (Table ).…”
Section: Discussionsupporting
confidence: 89%
“…stover incorporation and roots, as can be seen for the mineral fertilizer treatment (Table ). This is the key point of our research which distinguishes it from the works of others authors (Whalen & Chang, ; Hou et al, ; Tripathi et al, ; Gelaw et al, ; Mikha et al, ) where soil aggregation was related to total SOC. It also reinforces the warning of Pulido Moncada et al () when using the SOC as an estimator of aggregate stability, that specific fractions of the SOC can be the stabilizing agent as, in our case, the light fraction despite the increment of the most stable SOC fraction at the highest manure rate (Table ).…”
Section: Discussionsupporting
confidence: 89%
“…The previous investigation had shown that aromatic C in composted dairy manure accounted for approximately 30 % of the total C, taking advantage of the solid-state 13 C nuclear magnetic resonance (NMR) spectroscopy (Liang et al, 1996). And the addition of manure-based amendments increased SOC and enhanced aggregate stability (Mikha et al, 2015). But it is unclear whether manure is directly contributed to aromatic C increase or first utilized by microbes and then contributed to aromatic C increase in this study.…”
Section: Long-term Organic Fertilization Increased the Concentrationmentioning
confidence: 78%
“…The positive effects of FYM and NPKS on aggregate stability may be attributed mainly to the improvement of soil organic carbon through a greater amount of organic inputs. Mikha et al (2010) [75] pointed out that long-term manure application promoted the formation of macro-aggregates and increased aggregate stability. Also, amendments may indirectly affect aggregate stability by increasing crop productivity and biological activity.…”
Section: Aggregate Stability and Its Relationship With Other Propertiesmentioning
confidence: 99%